Determinants of Firm Value in Indonesia: Financial Factors or Non Finan-cial Factors? - Pujiati, Diyah; Averina, Maria (Future Science / FSH-PH Publications, 2022)
Firm value plays an important role for public companies because it can affect investor perceptions. The company is always trying to improve the quality of the company to be able to compete in the capital market to attract investors. The success of the company can only be achieved through good company management, improving company performance, so that in the end it can increase company value. This study aims to examine the factors that affect firm value in Indonesia. The factors used in this study are corporate social responsibility, environmental disclosure, ownership concentration, and earnings quality. The research sample is manufacturing companies on The Indonesia Stock Exchange with a research period of 2017-2019. The research sample consists of 127 observations. Data were analyzed using linear regression. The results of this study show that corporate social responsibility, environmental disclosure, and ownership concentration affected firm value, while earnings quality did not affect a firm's value in Indonesia. This study implies that non-financial factors determine to firm's value more than financial factors.